Ist das österreichische Rentensystem nachhaltig? - Florian Blank; Camille Logeay; Erik Türk; Josef Wöss; Rudolf Zwiener (Wirtschaftsdienst, 2018)
In der deutschen Debatte zur Rentenpolitik wird in letzter Zeit immer wieder auf das Beispiel Österreich verwiesen. Das hohe österreichische Leistungsniveau provoziert Nachfragen, auch nach der Nachhaltigkeit seiner Finanzierung, die teils infrage gestellt wird. In diesem Beitrag werden nach einer kurzen Einführung in das österreichische System unterschiedliche Aspekte der Nachhaltigkeit analysiert. Es wird gezeigt, dass die Vorwürfe, das österreichische Rentensystem sei nicht nachhaltig, ohne wissenschaftliches Fundament sind. – – Are the very high replacement rates of the Austrian pension insurance sustainable in the long run? This paper looks at different aspects of sustainability. The authors discuss the long-term expenditure path of the Austrian pension system as projected by the European Commission, analyse the Mercer index of sustainability and the concept of 'implicit public debt'. Furthermore, they lo ok at the impact of demographic change and wage costs for the Austrian pension system and at the role of public subsidies. Finally, s ome questions of intergenerational justice are analysed. The authors show that the Austrian pension system is sustainable.
Keywords: H55; J26; J32; 330